2017
DOI: 10.1016/j.concog.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relations among mindfulness facets and various meditation practices: Do they work in different ways?

Abstract: a b s t r a c tSeveral meditation practices are associated with mindfulness-based interventions but little is known about their specific effects on the development of different mindfulness facets. This study aimed to assess the relations among different practice variables, types of meditation, and mindfulness facets. The final sample was composed of 185 participants who completed an on-line survey, including information on the frequency and duration of each meditation practice, lifetime practice, and the Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…For instance, the accumulated total lifetime of focused-attention meditation practice had a predictive effect only on the sub-component acting with awareness as measured with the Five Facet Mindfulness Questionnaire (FFMQ). Given that acting with awareness involves focusing on the current activity rather than automatically engaging in it, this sub-component seems to share similarities with the factor presence measured with the FMI; thus, our results are consistent with Cebolla's et al (2017) [68] findings. Although only the negative association between the sub-factor acceptance and the DDFS scores appeared to be significantly related to the observed attenuation in the frequency of mind-wandering in daily life, the comparison between the r acceptance/DDFS coefficient and the r presence/DDFS coefficient were not statistically different.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, the accumulated total lifetime of focused-attention meditation practice had a predictive effect only on the sub-component acting with awareness as measured with the Five Facet Mindfulness Questionnaire (FFMQ). Given that acting with awareness involves focusing on the current activity rather than automatically engaging in it, this sub-component seems to share similarities with the factor presence measured with the FMI; thus, our results are consistent with Cebolla's et al (2017) [68] findings. Although only the negative association between the sub-factor acceptance and the DDFS scores appeared to be significantly related to the observed attenuation in the frequency of mind-wandering in daily life, the comparison between the r acceptance/DDFS coefficient and the r presence/DDFS coefficient were not statistically different.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that formal training in mindfulness leads to both state and trait changes in mindfulness [66,67]. Different forms of attention regulation in meditation (e.g., focused attention and open monitoring) and variables in its practice (e.g., total lifetime meditation practice, frequency of practice, and minutes of practice) have been associated with specific facets of the trait-mindfulness [68]. For instance, the accumulated total lifetime of focused-attention meditation practice had a predictive effect only on the sub-component acting with awareness as measured with the Five Facet Mindfulness Questionnaire (FFMQ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has pointed to the key role of informal mindfulness in developing the ability to pay attention to internal and external experiences. Cebolla et al found frequency of informal practice predicted the “observing” facet of mindfulness as measured by the Five Facet Mindfulness Questionnaire (Cebolla et al 2017 ). The evidence regarding the effects of informal mindfulness is therefore unclear, and Crane et al ( 2014 ) suggest that further research is needed before conclusions can be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…Compassion is a construct closely related to mindfulness 20 and can be defined as the desire to alleviate the suffering and its causes in one’s self and those around us. 21 When compassion is directed toward oneself, it is called self-compassion.…”
Section: Introductionmentioning
confidence: 99%
“…Like mindfulness, compassion can be trained using specific techniques and procedures (compassion-based interventions [CBIs]) designed to specifically generate cognitive and emotional compassionate habits. 20 Some authors have argued that CBIs could provide useful skills to treat and prevent several psychological difficulties (resources for interpersonal relationships, reduction of depressive symptomatology, reduction of social anxiety, marital conflict, and anger management and deal with the difficulties of being a caregiver). 24 In addition, evidence points out that CBI has been associated with decreased inflammatory responding to a psychosocial stressor.…”
Section: Introductionmentioning
confidence: 99%